Iqra Method: Improving Ability to Read and Write the Qur'an - Rifdah Fadilatul Munawaroh; Imam Tabroni; Dian Rahmawati; Safarotunnajah; Dean Dwi Putra (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
This article aims to discuss the ability to read and write the Qur`an in grade 5 SDIT Kharisma Darussalam, this study uses a correlational analysis descriptive research method, namely research conducted to get a picture of a reality. The results of this study state that the recitation of the Qur'an must be in accordance with good and correct principles by continuing to harm by reading and writing. In studying the Qur'an it is necessary to know the hijaiyah letters and also how to write them as in the iqra method from hijaiyah letters to short verses in the Qur'an. Because understanding reading and writing the Qur'an is important for every Muslim as a guide in life.